Registration of Two CS‐B17‐derived Upland Cotton Recombinant Inbred Lines with Improved Fiber Micronaire. Issue 1 (23rd August 2017) - Saha, Sukumar; Jenkins, Johnie N.; McCarty, Jack C.; Hayes, R. W.; Stelly, David M.; Campbell, B. T.
Abstract : A population of 50 chromosome‐specific cotton ( Gossypium hirsutum L.) recombinant inbred lines (RILs), CS‐B17 RILs, was developed by inbreeding an F1 hybrid between 'TM‐1', the genetic standard line of upland cotton ( G. hirsutum ), and CS‐B17, a formally released interspecific chromosome substitution line. The parents, CS‐B17 and TM‐1, are genetically similar for all chromosome pairs except chromosome 17, which in CS‐B17 was replaced by chromosome 17 of 3‐79 ( G. barbadense L.). Two CS‐B17 RILs, CS‐B17‐RIL‐59 (Reg. No. GP‐1021, PI 677340) and CS‐B17‐RIL‐98 (Reg. No. GP‐1022, PI 677342), were selected and released on the basis of their improved fiber quality traits, especially their favorable low micronaire values of 3.96 and 3.86, respectively, compared with the commercial lines 'DP 393' and 'PHY 370 WR', which had micronaire values of 4.52 and 4.58, respectively. However, the agronomic traits of the commercial lines were better than the released CS‐B17 RILs. Fiber with a micronaire value in the range of 3.7 to 4.2 is considered as the base range in the textile market, whereas US‐produced cotton averaged 4.40 over the past decade. These germplasm lines may provide genetic variation from G. barbadense that can be used to enhance cotton fiber quality of upland cotton.